PENGARUH E – SERVICE QUALITY DAN PRODUCT QUALITY TERHADAP INTENT TO ONLINE REPURCHASE MELALUI E – SATISFACTION SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA MAHASISWA FAKULTAS ILMU SOSIAL DAN POLITIK UNIVERSITAS DIPONEGORO SEMARANG) - Abdi Filadelfia Prakarsa Purba; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2016)
Fashion Product is one of the necessities of human clothing. However, today,s fashion need has become a basic requirement for some people. Prospective costumers want speed and ease of finding information about fashion and make purchases. With the development of internet technology, which brings convenience for everyone, not just to communicate but also to conduct business transactions anytime and anywhere. Trading activities can now be done through a virtual world that is now known as E – Commerce.This study conducted on students of the faculty of social science and politics have ever made a purchase online. This study aimed to examine the effect of E – Service Quality and Product Quality to The Intent Of Online Repurchase through E – Satisfaction as an intervening variabel.In this study, the data collected by questionnaire to 100 respondents taken by accidental sampling using a sampling technique of non – probability sampling with no opportunity or equal opportunity for each element or member of the population.Based on the analysis of two – stage regression model, it is known that increasing E – Satisfaction caused by the rise of E – Service Quality and Product Quality may increase Intent To Online Repurchase products online fashion.A suggestion in this study in which the company,s online shop should keep a service quality and product quality that they have such as easy access to iformation, ease of navigation, the hospitality staff service, reliability and durability of the products, information security and privacy so that customers who purchase products online fashion be satisfied in doing online shopping and the future return to purchase products online fashion.